Employee Workload Analysis Using the Full Time Equivalent Method in the Production Division at PT. Indonesian Ship Industry (Persero) Makassar - Mazitah, Nurfaidah; Dahlan, Muhammad; Ahmad, Arfandi; Mahendra, Kresna Adi (PT. SAFARI AMALIA, 2023)
PT. IKI is a shipbuilding company owned by the Indonesian government engaged in production. Preliminary observations found that there was an imbalance in the workload received by each employee, causing employees to work beyond operating hours, sometimes also working outside the company's working days. Workload analysis is very important to calculate exactly how many employees are needed to complete all tasks in a part or department in the company. In this research was conducted to identify the workload received by employees of the plumbing department, and determine the number of employee needs based on their workload. This study uses the full time equivalent method to identify the workload received by employees and determine the number of employee needs based on their workload. The results of this study indicate that there is an uneven workload at one work station, where from the results of calculations using the FTE method it is known that the workload of employees 1 and 2 is classified as overload and employees 3, 4, 5, 6, 7, 8, 9, and 10 in the normal category. Based on the results of this study, the number of employees was increased, namely 2 people. So the optimal number of employees is 12 people. Another suggestion is for employees who experience an overloaded workload or an uneven workload at one work station, then some of the job descriptions for employees who have an overloaded workload are given to employees who have a normal workload.